Color tuning of up-conversion emission in ytterbium, erbium, aluminum tri-doped zinc oxide crystal by adjusting aluminum concentration. Issue 1 (2nd January 2018) - Zhang, Zhirong; Xu, Yanling; Li, Yuemei; Zheng, Wei; Zhao, Zhenni; Wang, Rui
ABSTRACT: Ytterbium, erbium, aluminum tri-doped zinc oxide crystal was synthesized, which can turn color from red to green up-conversion luminescence through adjusting aluminum content. When the aluminum concentration reached 4 mol%, the color of up-conversion emission first turn from red to green. Meanwhile, the ratio of red to green emission reduced from 25.32 to 0.26, and the coordinates of chromaticity coordinate calculation changes from (0.5749, 0.3378) to (0.2190, 0.7169) with aluminum concentration range from 0 to 4 mol%. The up-conversion emission peaks at 521, 542, and 660 nm of sample originate from the transitions of 2 H11/2 → 4 I15/2, 4 S3/2 → 4 I15/2, and 4 F9/2 → 4 I15/2 of erbium ions, respectively. X-ray diffraction patterns perform the better crystallization degree with increasing aluminum concentration. The scanning electron microscopy images show the porous and lamellar structures with different aluminum concentrations. A convenient but effective design to obtain ytterbium, erbium, aluminum tri-doped zinc oxide up-conversion luminescence is reported, which can turn color from red to green.